INDONESIAN NATIONAL DEFENSE MANAGEMENT (STUDY ON THE STUDY OF THE CONTENT AND SUBSTANCE OF INDONESIAN DEFENSE REGULATION POLICY) - Raja Humuntal Manalu; Siswo Hadi Sumantri; Suyono Thamrin; Pujo Widodo (UNIVERSITAS PAKUAN, 2022)
The development of social life and technological progress of each country has the potential to have positive and negative impacts on other countries. The state as a legal instrument that functions to protect and prosper citizens against threats from internal and external. For every country, a national defense system is needed that is able to manage all potentials to become a positive value for national defense. This paper aims to explore the management of the Indonesian state defense. This paper is a qualitative type with a descriptive method. Documentation and literature studies were chosen to reach answers in this research. Regulatory analysis related to Indonesian national defense is used to examine the content and substance. The data and information are obtained through a study of the Law of the Republic of Indonesia Number 3 of 2002 concerning National Defense, the Law of the Republic of Indonesia Number 16 of 2012 concerning the Defense Industry and the Law of the Republic of Indonesia Number 23 of 2019 concerning the Management of National Resources for National Defense. This paper finds that the management of the Indonesian state defense is realized through the concept of a defense system, defense industry and management of national resources that are integrated with each other.